Emergency preparedness for mass gatherings: Lessons of “12.31” stampede in Shanghai Bund - Yong-He Dong; Fei Liu; Yong-Mei Liu; Xia-Rong Jiang; Zhong-Xin Zhao (Chinese Journal of Traumatology, 2017)
According to WHO, one of these mass gatherings with critical risk is stampedes. Shanghai “12.31” stampede was a preventable tragedy that the government and event planner hold responsibility for. At the same time, it can be a legacy for improvement in the future. The government should draw experience on the implementation of an emergency preparedness system, in order to improve the rapid emergency response during mass gatherings in the future.